2019
DOI: 10.1177/1073191119890030
|View full text |Cite
|
Sign up to set email alerts
|

Child Maltreatment Severity Questionnaire (MSQ) for Professionals: Development, Validity, and Reliability Evidence

Abstract: This article presents the development and validation of the child Maltreatment Severity Questionnaire (MSQ), aiming to contribute to increase the quality and efficiency of evaluation processes in the Child Protection System (CPS). To obtain a valid and reliable instrument, a set of studies was developed: Study 1—Based on two previous studies, the questionnaire was developed and the severity level of the items within maltreatment subtypes was assigned by 93 professionals from the welfare and CPS system. Consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…To measure pre-care parental maltreatment, the case manager of each youth completed the Child Maltreatment Questionnaire ( Calheiros et al, 2021 ). This questionnaire is composed of 19 items organized in four dimensions: Neglect – lack of physical provision, Physical and psychological abuse, Emotional and educational maltreatment, and Neglect – lack of supervision.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure pre-care parental maltreatment, the case manager of each youth completed the Child Maltreatment Questionnaire ( Calheiros et al, 2021 ). This questionnaire is composed of 19 items organized in four dimensions: Neglect – lack of physical provision, Physical and psychological abuse, Emotional and educational maltreatment, and Neglect – lack of supervision.…”
Section: Methodsmentioning
confidence: 99%
“…This questionnaire is composed of 19 items organized in four dimensions: Neglect -lack of physical provision, Physical and psychological abuse, Emotional and educational maltreatment, and Neglect -lack of supervision. This measure has been tested in previous studies and has shown good psychometric properties, namely, adequate model fit (χ 2 /df = 3.52, CFI = 0.905, GFI = 0.905, TLI = 0.886, RMSEA = 0.072) and reliability (Neglect -Lack of provision α = 0.76, Neglect -Lack of supervision α = 0.84, Emotional and Educational Maltreatment α = 0.76, and Physical and Psychological abuse α = 0.81; Calheiros et al, 2021). In the final part of the questionnaire, based on item evaluation and on the information available in the youth's record, the professionals were asked to evaluate on a yes/no scale if the youth was subjected to neglect, physical or psychological abuse, or sexual abuse.…”
Section: Previous Maltreatmentmentioning
confidence: 99%
“…Child and adolescent maltreatment. Children and adolescents’ maltreatment experiences were measured through the Child Maltreatment Severity Questionnaire (MSQ; Calheiros et al, 2019), filled out by the CYPC case workers based on the information they had gathered regarding each participating child/adolescent. The MSQ consists of 18 items, each with 4 descriptors, which were rated by the case workers using a 5-point scale (1 = unknown/never occurred; 2 = a little severe; 3 = moderately severe; 4 = highly severe; 5 = extremely severe).…”
Section: Methodsmentioning
confidence: 99%
“…These reports were obtained through the Maltreatment Severity Questionnaire (MSQ; Calheiros et al, 2019), consisting of 21 items (e.g., Physical hygiene and wellbeing ), each composed by four severity descriptors (e.g., from 1 = They keep the child looking dirty [ e.g., does not take a bath, does not wash her head or teeth, stinks, has parasites and/or fleas ] to 4 = They let the child have health problems or injuries due to her hygienic conditions [ e.g., skin diseases, infected skin injuries ]). Originally, the MSQ is organized in a three-factor structure: Physical neglect, Psychological neglect, and Physical and psychological abuse.…”
Section: Methodsmentioning
confidence: 99%